Factors affecting sustainable clothing purchase intentions: evidence from Indonesia - Arqam Afifah Nurul Azizah Ruhul; Amar Kifayah; Syamsul Nadzirah Ikasari; Bahri Syamsul; Mangngenre Saiful (Engineering Management in Production and Services)
The purpose of this study is to contribute to the debate over whether the Theory of Planned Behavior, in conjunction with several other variables, can increase purchase intention for sustainable clothing in Indonesia. A survey questionnaire was used to collect data. A total of 502 responses were received from Indonesians who are sustainable clothing customers. Among the variables examined using SEM, only perceived consumer effectiveness and subjective norm were shown to have a positive-significant effect on Indonesians’ purchase intentions, whereas the remaining variables, including the moderated variables, had no effect. The findings of this study will assist industry professionals in developing strategies for more effective customer communication aimed at promoting desirable purchasing behaviour.